The varieties of the psychedelic experience : a preliminary study of the association between the reported subjective effects and the binding affinity profiles of substituted phenethylamines and tryptamines - Zamberlan, Federico (2018)
Fil: Zamberlan, Federico. Universidad de Buenos Aires. Departamento de Física; Argentina